PENDAMPINGAN DALAM PEMBUATAN KONTEN MELALUI MEDIA SOSIAL INSTAGRAM NAFISAH TOUR TRAVEL - Al Hafidz, Thariq Naufaldy; Firmandinesta, Adrian; Istiqomah, Istiqomah (Universitas Sanata Dharma, 2025)
PT Nafisah Indo Permata is a travel agency company, especially for Umrah, Hajj, and other pilgrimage or spiritual trips. This company promotes its umrah and hajj travel, Nafisah Tour Travel, using direct selling methods—distributing brochures and business cards—while using a digital marketing strategy through Instagram. Unfortunately, Nafisah Tour Travel faces several problems, specifically in that it cannot maximize digital marketing as a promotional strategy for its umrah and hajj travel agencies. To overcome this problem, community service activities were conducted by Universitas Muhammadiyah Sidoarjo (UMSIDA) to assist Nafisah Tour Travel’s team in improving the quality of content produced on Instagram. In addition, it helped increase the credibility and reach of the Nafisah Tour Travel Instagram account. The result of this activity was the increasing reach of Nafisah Tour Travel through Instagram.